2016
DOI: 10.1149/2.0141610jes
|View full text |Cite
|
Sign up to set email alerts
|

N, La Co-Doped TiO2for Use in Low-Temperature-Based Dye-Sensitized Solar Cells

Abstract: In this survey, N, La co-doped TiO 2 nanocrystals are synthesized through simple sol-gel method. Results reveal that both elements of N and La are introduced successfully into the structure of TiO 2 and exist as the form of La (Ti-O-La) bonds, N (N-Ti-O) bonds and N (Ti-O-N) bonds by several characterization analysis, thereby resulting in the formation of new impurity energy level between the forbidden bands, and great enhancement of light absorption ability in visible light region. These resulting samples are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Even though the dip-coating method was used several times to deposit layers of sufficient thickness, the entire coating had to be processed in an oven at 120 °C for 1 h, which is quite a long time if roll-to-roll processing is envisaged. Similarly, Y. F. Jiang et al 11 used the doctor-blade technique to deposit an N−La codoped TiO 2 photoanode, which had to be further processed at 120 °C for 30 min to eliminate volatiles, still an extended period for convenient roll-to-roll processing. Silica has been successfully employed as a binder for passive photocatalytic coatings 12 and, despite its inherently insulating nature, it has proved useful for titania photoanodes as well.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the dip-coating method was used several times to deposit layers of sufficient thickness, the entire coating had to be processed in an oven at 120 °C for 1 h, which is quite a long time if roll-to-roll processing is envisaged. Similarly, Y. F. Jiang et al 11 used the doctor-blade technique to deposit an N−La codoped TiO 2 photoanode, which had to be further processed at 120 °C for 30 min to eliminate volatiles, still an extended period for convenient roll-to-roll processing. Silica has been successfully employed as a binder for passive photocatalytic coatings 12 and, despite its inherently insulating nature, it has proved useful for titania photoanodes as well.…”
Section: Introductionmentioning
confidence: 99%
“…The classification of dopants based on general electronic configuration falls into alkaline earth metals [94][95][96] , metalloids [97][98][99] , non-metals [100][101][102] , transition metals 103 , post-transition metals 104,105 and lanthanides [106][107][108] . Significant attempts were made for co-doping in which more than one dopant is introduced into the lattice for enhanced device performance [109][110][111] . Doping in TiO 2 lattice alters its phase, flat band potential, recombination rate, electron transport rate and dye adsorption capability 79 .…”
Section: Tio 2 Photoanode Modification By Dopingmentioning
confidence: 99%
“…Xie et al in 2012 presented the feasibility of luminescence conversion and RE ions as p‐type dopants leading to elevation of Fermi‐level of the oxide films, thus enhancing the photovoltage of the DSSCs. Therefore, solar conversion efficiency was enhanced in DSSCs containing RE ions as compared with DSSCs lacking RE ions. The authors reported that Tm 3+ /Yb 3+ ions act as luminescence medium and transfer infrared light into visible light through an upconversion luminescence process, which leads to improvement in incident light harvesting as well as enhanced photocurrent of RE‐doped DSSCs. In 2017, Fouad et al reported that with increasing Eu doping concentration optical absorption/fluorescence was enhanced and this resulted in an increase in the FWHM of peaks as well as photoconversion efficiency .…”
Section: Re‐doped Tio2 For Spectral Conversionmentioning
confidence: 99%
“…The authors reported that Tm 3+ /Yb 3+ ions act as luminescence medium and transfer infrared light into visible light through an upconversion luminescence process, which leads to improvement in incident light harvesting as well as enhanced photocurrent of RE‐doped DSSCs. In 2017, Fouad et al reported that with increasing Eu doping concentration optical absorption/fluorescence was enhanced and this resulted in an increase in the FWHM of peaks as well as photoconversion efficiency . It is observed that photoanode layer of Eu‐doped TiO 2 enhances efficiency as compared to undoped TiO 2 and this important property of doping plays an important role in altering the material for DSSCs to exhibit better performance . Figure represents the fabrication of DSSCs with Eu‐doped TiO 2 as photoanode, distinctly showing dye absorption, electrolyte reduction and oxidation, electron‐injection and conduction process …”
Section: Re‐doped Tio2 For Spectral Conversionmentioning
confidence: 99%